Characterization of breast cancer DNA content profiles as a prognostic tool - Gerashchenko, B.I.; Huna, A.; Erenpreisa, J. (Experimental Oncology, 2014)
Worldwide, breast cancer in women remains to be the most common malignancy that in a considerable proportion shows the resistance to genotoxic treatments and poor outcome. Chromosomal instability manifested as aneuploidy represents an integral characteristics of the malignant genotype not only because of the selection of mutated aneuploid sub-clones that stipulate the tumor progression, but also because of the reversible endopolyploidy of tumor cells that serves for the endless maintenance of therapy-resistant tumor stem cells. Therefore, cytometric determination of DNA content in tissue samples for detecting malignancy, monitoring responses to therapy, and prognosing disease outcome needs to be revived. Both flow and image cytometry are most frequently used for generation of DNA content profiles (histograms), interpretation of which, however, may have some caveats. This review presents the major characterization criteria and analysis tools for breast cancer DNA histograms. Key Words: breast cancer, aneuploidy, DNA content analysis, DNA histogram, flow cytometry, image cytometry.